Develop Comics as Learning Media to Improve Students’ Knowledge about Environmental Disaster in Biology Learning - Indri Yani; Lufty Hari Susanto; Ilmi Zajuli Ichsan; Giry Marhento (Jurnal Penelitian Pendidikan IPA, 2023)
The development of innovative learning media is an alternative to solving problems that occur in the learning process, especially for students in biology learning. For this reason, an innovation in learning is needed to increase students' knowledge about environmental disasters and the handling of various types of environmental disasters through environmental disaster comics. The research method used is Research & Development (R&D) and uses the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation) with a one group pretest - posttest research design. The subjects in this study were class VII students of MTs Ar-Ridho Sentul. The research instrument used was in the form of multiple-choice questions and questionnaire sheets. Data analysis techniques include assessing creative thinking skills which are measured using the N-Gain formula. The results of the data analysis showed that the students' knowledge increased significantly. This indicates that project-based learning comic-based learning media is able to increase students' knowledge. In addition, the response of teachers and students also gave positive results that learning media in the form of comic project based learning can help increase knowledge of environmental disaster mitigation.